Association between systemic immune-inflammation index and low muscle mass in US adults: a cross-sectional study - Lin Shi; Liang Zhang; Dan Zhang; Zhuo Chen (BMC, 2023)
Abstract Background Chronic inflammatory responses have been reported to be associated with low muscle mass and systemic immune-inflammation index(SII) is a novel indicator of inflammation. The purpose of our study was to clarify the relationship between SII and low muscle mass. Methods This study was a cross-sectional study based on National Health and Nutrition Examination Survey (2011-2018). SII was calculated as the platelet count × neutrophil count/lymphocyte count. Appendicular skeletal muscle index was used to define low muscle mass. The individuals were divided into four groups by the quartile of SII (Q1-Q4). Multivariate weighted logistic regression analysis, smooth curve fitting and subgroup analysis were used to investigate the relationship between SII and sarcopenia. Subgroup analysis were based on demographic and clinical variables. Results There were 10,367 individuals enrolled in our final analysis. The overall mean age was 39.39 years and 49.17% were males. The overall prevalence of low muscle mass in the study population was 8.77%. The smooth curve fitting analysis indicated a near-linear relationship between SII and low muscle mass. In multivariate weighted logistic regression analysis, the odds ratio (OR) of Q4 is 1.28 (95% CI, 1.16-1.40) for low muscle mass when compared to lowest quartile of the SII. In subgroup analysis, SII still increased the risk of low muscle mass independently. Conclusion The increased SII levels were associated with an increased risk of low muscle mass in a large population. Our study increased the understanding between inflammation and low muscle mass. Anti-inflammation therapy may be important for low muscle mass.